Teaching Bioethics at the Secondary School Level - Bishop, Laura J. (The Hastings Center report, 2015)
Recognition that it is both possible and important to teach secondary school students about bioethics issues and theory has grown slowly within the field of bioethics. In the late 1970s and 1980s, a few first-generation pioneers recognized the teaching and learning opportunities inherent in bioethics and obtained pilot grants to educate high school teachers about bioethics issues. In the 1990s and 2000s, second-generation efforts explored the possibilities of bioethics in secondary schools using a range of approaches, models, and funding sources. A third generation of programs that are now emerging benefits from more stable funding and offers materials that may be accessed by teachers across a country or around the world; a number of these programs are endorsed by national entities. An historical overview of these efforts to teach bioethics in high schools highlights some essential steps that must be taken to meet the challenge of teaching bioethics in pre-college settings.